Issue Notes - , Editor (Historical Papers, 2022)
1. The paper presented by Lawrence Nixon, “Changing Trends in Manitoba Religion,” is forthcoming in A Geography of Manitoba: Its Land and People, eds. John Welsted, John Everitt and Christoph Stadel (Winnipeg: Univ. of Manitoba Press). 2. The papers presented by Paul Laverdure, David Seljak and Marguerite Van Die were not made available for publication.